Experience of Mindfulness Meditations Based on Stress Reduction among Undergraduate Nursing Students, Chitwan, Nepal - Pandey BistaArchana; AdhikariJamuna; ShahBimala Kumari; Poudel Kalpana; KC Bhagwati; Pandey, Apsara (Journal of Nepal Health Research Council, 2024)
Background: Undergraduate nursing students are frequently vulnerable to stress during their education with a high rate of attrition. Mindfulness Mediations based on Stress Reductions have been found to promote psychological well-being and mental health among nursing students. Therefore, the objective of the study was to explore the experiences of Mindfulness among undergraduate nursing students. Methods: Qualitative Hermeneutic Phenomenology research design was adopted. Data were collected from under graduate nursing students from Chitwan Medical College, Institute of Medicine who had been practicing Mindfulness Meditation for 6 weeks. The duration of data collection was January to June 2022. Data were collected after obtaining ethical approval from Nepal Health Research Council. Focused Group Discussions were conducted to collect data by the researcher using the Focused Group Discussion guide in Nepali language. A total of three Focused Group Discussions was carried out among 12 participants in each Focused Group Discussion with a total of 36 participants. Data were analyzed by thematic analysis technique based on Giorgi’s qualitative data analysis technique. Results: Five developed themes were stress managed well in daily life and during examination time, present moment awareness and positivity, self-realization of inner peace and more self-acceptance, and feeling of developed future role for advocating mindfulness meditations. Conclusions: Mindfulness-based mediations have been found effective strategies among undergraduate nursing for the management of stress during daily living and during examinations, development of self-realization, increase inner peace, self-acceptance and developed skills for future role for advocating mindfulness meditations. Keywords: Mindfulness meditations; nursing students; stress.